A Functional Near Infra-red (fNIRS) Neurocorrelate of Loss of Control Eating (P08-017-19). (24th October 2019) - Thomopoulos, Dimitra Kristina; Albajri, Eram; Lanza, Lisa; Ayaz, Hasan; Parigi, Angelo Del; Nasser, Jennifer
Abstract: Objectives: Embedded within a study examining regional prefrontal cortex activation during eating, we assessed loss of control over eating by questionnaire, and hypothesized that medial prefrontal cortex (mPFC) activity measured during eating preferred food would be greater in those self-reporting "Loss of Control" (LOC) over eating. Methods: Seventy adults (34 M, 36 W) completed the TFEQ, BES and two LOC questionnaire (EDE-Q and Latner LOCES), had anthropometrics measured, and consumed a self rated preferred food in one session, and a self rated non-preferred food in another, while wearing a fNIRS headband sensor. Order of food session was randomized between participants. The ad libitum eating episode lasted between 3 and 10 minutes. Two groups were formed based on whether fNIRS data showed mPFC activation was greater or less than lPFC activation. LOC scores where compared between fNIRS groups. Results: The LOC score (EDE-Q) was higher for the mPFC > lPFC group ( P  = 0.041, controlled for BMI). The LOC (Latner LOCES) was also higher for the mPFC > lPFC group ( P  = 0.05, controlled for BMI and sex). There was no significant correlation between LOC scores and anthropometric measures, food intake, or TFEQ, or BES scores. EDE-Q and LOCES were significantly correlated in a quadratic relationship ( P  = .018). Conclusions: LOC questionnaires appear to reflect subjective feelings of loss of control, as opposed to objective consequences (BMI, waist circumference, food intake) of loss of control. fNIRS activation provides a demonstration of a potential objective measure of subjective feelings. As EDE-Q and LOCES do not correlate linearly, the use of an objective instrumental measure may prove more useful in diagnosing LOC. Funding Sources: Funding was provided by the Clinical Translational Research Institute of Drexel University.